Larvicidal activities of the leaf extracts and essential oil of Premna latifolia Roxb. (Verbenaceae) against Aedes albopictus Skuse (Diptera: Culicidae) - Renjana P. K. and John E.Thoppil (Journal of Applied Pharmaceutical Science, 2013)
In the context of rapid emergence of resistance among vector mosquitoes to synthetic insecticides, use of natural products of plant origin has gained considerable importance as potential agents for vector control. The current investigation attempts to evaluate the mosquito larvicidal efficacies of the crude aqueous, chloroform and methanol extracts and essential oil from the leaves of Premna latifolia Roxb. (Verbenaceae) against the fourth instar larvae of Aedes albopictus Skuse (Diptera: Culicidae). The chemical composition of essential oil also was analyzed using gas chromatography–mass spectrometry. The extracts as well as the essential oil showed good larvicidal effects; however, the highest larval mortality was found in essential oil followed by chloroform extract. Their LC50 values in 24 h were 38.9 ppm (LC90 = 86.9 ppm) and 76.1 ppm (LC90 = 272.1 ppm) respectively. The principal chemical constituents found in the essential oil were β-cadinene (33.62%) and phytol (27.28%), followed by α-selinene (9.42%). The study demonstrates that crude extracts and essential oil of P. latifolia leaves have good potential to be used as biodegradable agents for the control of the mosquito vector A. albopictus and could be a potent source for the production of biodegradable natural larvicides.
Keywords: Aedes albopictus, Larvicidal, Premna latifolia, Esse